Monocrystalline sodium ion layered oxide material, preparation method thereof and secondary battery
By controlling the crystal structure of single-crystal sodium ion layered oxide materials, especially the half-maximum width of the crystal planes of 003 and 104, a material with a specific crystal plane size was prepared, which solved the problem of structural phase change in the material during charging and discharging, and improved the cycling performance and battery life.
Patent Information
- Application Number
- CN202411809041.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
Single-crystal sodium ion layered oxide materials are prone to structural phase change during charging and discharging, resulting in a decrease in cycle life. The existing methods of doped elements to improve electrochemical performance cannot fundamentally solve the phase change problem.
By controlling the half-maximum width of the 003 crystal plane and the half-maximum width of the 104 crystal plane of the crystal structure, select the Ni, Fe, Mn content with certain parameters, and prepare a single crystal sodium ion layered oxide material with a specific crystal plane size to inhibit structural phase change.
It effectively suppresses the c-axis change amplitude of sodium ion layered oxide materials during charging and discharging, maintains the stability of the structure, and improves the circulation performance and the cycle life of the battery.
Smart Images

Figure BDA0005180067650000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a single crystal sodium ion layered oxide material and a preparation method thereof, and a secondary battery. Background Art
[0002] Based on the advantages of sodium-ion batteries such as superior low-temperature and rate performance, stable cycles and abundant raw sodium resources, the battery science community has paid extensive attention to the research on sodium-ion batteries. However, due to the low energy density of sodium-ion batteries, their main application scenarios are energy storage, two-wheeled vehicles and low-speed vehicle markets.
[0003] The positive electrode materials of sodium-ion batteries include layered oxides, Prussian compounds and polyanion compounds. Due to the feasibility of mass production and comprehensive cost considerations, layered oxides are currently the best choice for mainstream sodium-ion battery positive electrode material manufacturers, and their production process is basically the same as that of lithium-ion layered oxides.
[0004] Sodium ion layered oxides are divided into polycrystalline and single crystal. Polycrystalline sodium ion layered oxides are aggregates formed by multiple particles. During the charge and discharge process, they will come into contact with the electrolyte and produce a variety of side reactions that are harmful to the battery, which limits their application in sodium ion battery systems. In their applications, additives are usually required to be added to the electrolyte to stabilize battery performance. Single crystal sodium ion layered oxide materials have a smaller contact surface with the electrolyte and a stable structure. Compared with polycrystalline sodium ion layered oxides, they are not prone to drastic phase changes during the charge and discharge process, resulting in structural collapse. Therefore, single crystal sodium ion layered oxide materials are the preferred positive electrode materials in sodium ion battery systems.
[0005] Although the structure of single-crystalline sodium-ion layered oxide materials is more stable based on polycrystalline sodium-ion layered oxides, as the battery is recycled, single-crystalline sodium-ion layered oxide materials will also undergo drastic phase changes, resulting in structural collapse and dislocation, leading to a decrease in reversible capacity and a decrease in cycle life. Although the industry has improved the electrochemical performance by doping elements in single-crystalline sodium-ion layered oxide materials, this method cannot change the crystal structure and cannot fundamentally solve the phase change problem. Summary of the invention
[0006] Based on the above problems, the present invention provides a single crystal sodium ion layered oxide material and a preparation method thereof, and a secondary battery. The single crystal sodium ion layered oxide material controls the half-peak width of the 003 crystal plane and the half-peak width of the 104 crystal plane by selecting a crystal structure with certain parameters, thereby controlling the crystal plane size, so as to reduce the structural collapse and ectopicity caused by phase change, which are not conducive to the cycle life.
[0007] To achieve the above-mentioned object, the first aspect of the present invention provides a single crystal sodium ion layered oxide material. The chemical formula is NaNix Fe y Mn (1-x-y) O2, 0.15≤x≤0.60, 0.20≤y≤0.40, the half-peak width of the 003 crystal plane and the half-peak width of the 104 crystal plane of the crystal structure meet the following conditions: kλ / Radians(FWHM003) / Fes(Radiansθ 003 )≤d≤kλ / Radians(FWHM 003 -u) / Fes(Radiansθ 003 ),kλ / Radians(FWHM104) / Fes(Radiansθ 104 )≤d≤kλ / Radians(FWHM 104 -v) / Fes(Radiansθ 104 ), where d is the interplanar spacing, 0.5≤k≤1.0, 0.11≤λ≤0.16, uv≥0.005.
[0008] The inventors of the present invention have found that the probability of phase change in single-crystal sodium ion layered oxide materials during the cycle process is closely related to the crystal structure. By controlling the half-peak width of the 003 crystal plane and the half-peak width of the 104 crystal plane in the crystal plane structure to a certain range, the c-axis variation amplitude of the sodium ion layered oxide material during the charge and discharge process can be effectively reduced, and the structural phase change during the charge and discharge process can be effectively suppressed, so that the structure of the single-crystal sodium ion layered oxide material remains stable during the charge and discharge process, thereby improving the cycle performance.
[0009] Based on this, the inventors selected the chemical formula of the single-crystalline sodium ion layered oxide material as NaNi x Fe y Mn (1-x-y) O2, by controlling the content of Ni, Fe, and Mn (i.e., controlling the values of x and y) within a certain range, the 003 crystal plane half-peak width and the 104 crystal plane half-peak width of the crystal structure can meet certain conditions. When the 003 crystal plane half-peak width and the 104 crystal plane half-peak width meet this condition, the crystal plane structure can grow in a preferential orientation, thereby suppressing the c-axis change amplitude of the sodium ion layered oxide material during the charge and discharge process, and thus the structural phase change is suppressed.
[0010] In some embodiments, the particle size satisfies 4.0 μm ≤ Dv50 ≤ 20.0 μm.
[0011] In some embodiments, the thickness of the single layer is 0.5 to 2.0 μm.
[0012] In some embodiments, the structural phase transition during the charge and discharge process can be suppressed, and the changes in the unit cell parameters a, b, and c axes before and after the phase transition satisfy the relationship: Δc<(Δa+Δb) / γ, 1<γ<5.
[0013] In some embodiments, the specific surface area is 0.3 to 0.8 m 2 / g.
[0014] In some embodiments, the compacted density is 3.5 to 4.5 g / m 3 .
[0015] The second aspect of the present invention provides a method for preparing a single-crystalline sodium ion layered oxide material, comprising the steps of:
[0016] (I) Synthesis of Ni by coprecipitation reaction x Fe y Mn (1-x-y) (OH)2 precursor;
[0017] (II) The Ni x Fe y Mn (1-x-y) The (OH)2 precursor, sodium salt and flux are mixed and reacted at high temperature under oxidizing atmosphere.
[0018] In the preparation method of the present invention, a specific precursor is prepared by controlling the specific metal elements Ni, Fe and Mn to a certain amount, and the precursor is mixed with a sodium salt and a flux and reacted at a high temperature under an oxidizing atmosphere to obtain a NaNi x Fe y Mn (1-x-y) A single crystal sodium ion layered oxide material having a crystal structure of O2, 0.15≤x≤0.60, 0.20≤y≤0.40. The half-peak width of the 003 crystal plane and the half-peak width of the 104 crystal plane of the single crystal sodium ion layered oxide material satisfy certain conditions, so that the crystal plane structure can grow in a preferred orientation, thereby suppressing the change amplitude of the c-axis of the sodium ion layered oxide material during the charge and discharge process, thereby suppressing the structural phase change.
[0019] In some embodiments, the sodium salt includes one or more of sodium nitrate, sodium chloride, and sodium carbonate.
[0020] In some embodiments, the sodium salt accounts for about 1% of the Ni x Fe y Mn (1-x-y) 50-70% of the mass of (OH)2 precursor.
[0021] In some embodiments, the flux includes one or more of zirconium oxide, zirconium hydroxide, magnesium oxide, magnesium hydroxide, lanthanum oxide, lanthanum hydroxide, strontium carbonate, strontium hydroxide, titanium oxide, and titanium hydroxide.
[0022] In some embodiments, the flux accounts for about 1% of the Ni x Fey Mn (1-x-y) 0.1~3.0% of the mass of (OH)2 precursor.
[0023] In some embodiments, the oxidizing atmosphere is air or oxygen.
[0024] In some embodiments, the reaction temperature of the high temperature reaction is 850-1050°C.
[0025] In some embodiments, the heating rate of the high temperature reaction is 1 to 5°C / min. (6) The reaction time of the high temperature reaction is 8 to 20 hours.
[0026] The third aspect of the present invention provides the use of the aforementioned single crystal sodium ion layered oxide material or the single crystal sodium ion layered oxide material prepared by the aforementioned method for preparing the single crystal sodium ion layered oxide material in a sodium ion battery.
[0027] The fourth aspect of the present invention provides a secondary battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the positive electrode material comprises the aforementioned single crystal sodium ion layered oxide material or a single crystal sodium ion layered oxide material prepared by the aforementioned method for preparing the single crystal sodium ion layered oxide material. DETAILED DESCRIPTION
[0028] The secondary battery of the present invention comprises a positive electrode material, a negative electrode material and an electrolyte. The preparation process of the secondary battery is similar to that of a lithium-ion battery, by first preparing a positive electrode sheet containing a positive electrode material and a negative electrode sheet containing a negative electrode material, then winding or stacking the positive electrode sheet, the negative electrode sheet and the separator into a bare cell, filling the cell with an electrolyte and sealing the cell in a housing.
[0029] Among them, the negative electrode sheet is obtained by coating the negative electrode slurry containing negative electrode active material, binder and conductive agent on the negative electrode collector, drying, cold pressing and die cutting. The mass ratio of negative electrode active material, binder and conductive agent can be 85-99:0.5-15:0.5-10. The negative electrode active material includes at least one of carbonaceous negative electrode material, silicon-based negative electrode material and silicon-carbon composite material. The carbonaceous negative electrode material can be but not limited to graphite material, soft carbon and hard carbon. The silicon-based negative electrode material can be but not limited to SiO x or carbon-coated SiO x, 0≤x<2. The silicon-carbon composite material may be a composite of silicon powder and a carbon coating layer. The binder is used to improve the bonding between the negative electrode material particles and between the negative electrode material particles and the negative electrode current collector. The binder may be selected from at least one of polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, styrene-butadiene rubber and acrylated styrene-butadiene rubber. The solvent of the negative electrode slurry may be N-methylpyrrolidone or N-vinylpyrrolidone. The negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and the like.
[0030] The separator can be a conventional insulating porous polymer film or an inorganic porous film, specifically but not limited to: a single layer or a combination of multiple layers of polypropylene, polyethylene, aramid, polyimide and non-woven fabric separators, such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator or a polypropylene / polyethylene / polypropylene three-layer separator. An insulating layer that allows ions to pass but not electrons can be provided on the separator to prevent the secondary battery from short-circuiting when thermal shrinkage occurs. The thickness of the separator is 3μm to 50μm.
[0031] Similar to lithium-ion batteries, the liquid electrolyte used in sodium-ion batteries includes non-aqueous organic solvents, sodium salts and additives. The non-aqueous organic solvent is required to have a large dielectric constant, a low melting point, and a strong sodium ion conductivity, and can usually be a chain carbonate, a cyclic carbonate, a carboxylic acid ester or a lactone. The chain carbonate can be dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or methyl ethyl carbonate. The cyclic carbonate can be ethylene carbonate, propylene carbonate or butylene carbonate. The carboxylic acid ester can be methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate or ethyl propionate. The lactone can be γ-butyrolactone, butyl-decanoic acid ester, γ-valerolactone or γ-caprolactone. The sodium salt may be one or more of NaPF6, NaClO4, NaAlCl4, NaFeCl4, NaSO3CF3, NaBCl4, NaNO3, NaPOF4, NaSCN, NaCN, NaAsF6, NaCF3Fe2, NaSbF6, NaC6H5Fe2, Na(CH3)C6H4SO3, NaHSO4 and NaB(C6H5)4, and the concentration of the sodium salt is 0.2M to 2.0M. Additives may also be added to the electrolyte to improve battery performance, and the additives may account for 0.1% to at least 10% of the electrolyte mass. Including but not limited to one or more of vinyl sulfite (GS), fluoroethylene carbonate (FEC), vinyl carbonate (VC), vinyl carbonate (VEC), 1,3-propane sultone (PS), vinyl sulfate (DTD), 4-methylethylene sulfate, 4-propylethylene sulfate, propylene sulfate, 4-methylpropylene sulfate and 4-propylpropylene sulfate.
[0032] The preparation of the positive electrode sheet generally includes: applying the positive electrode slurry containing the positive electrode active material, the binder and the conductive agent to the positive electrode collector for drying, cold pressing and die cutting. The mass ratio of the positive electrode material, the binder and the conductive agent may be 85-98:1-15:1-15. The binder may be, for example, but not limited to, at least one of polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl pyrrolidone, styrene-butadiene rubber, acrylated styrene-butadiene rubber and epoxy resin. The conductive agent is used to improve the conductivity of the positive electrode, for example, but not limited to, carbon black, acetylene black, Ketjen black, carbon fiber and other carbon-containing materials, or metal powders or metal fiber materials such as copper, nickel, aluminum, silver, or conductive polymers such as polyphenylene derivatives, or mixtures thereof. The positive electrode collector may be aluminum foil. The solvent of the positive electrode slurry may be N-methylpyrrolidone or N-vinylpyrrolidone. The positive electrode material may adopt the single crystal sodium ion layered oxide material of the present invention.
[0033] The chemical formula of the single crystal sodium ion layered oxide material of the present invention is NaNi x Fe y Mn (1-x-y) O2, 0.15≤x≤0.60, 0.20≤y≤0.40. The half-peak width of the 003 crystal plane and the half-peak width of the 104 crystal plane of the crystal structure meet the following conditions: kλ / Radians(FWHM003) / Fes(Radiansθ 003 )≤d≤kλ / Radians(FWHM 003 -u) / Fes(Radiansθ 003 ),kλ / Radians(FWHM104) / Fes(Radiansθ 104 )≤d≤kλ / Radians(FWHM 104 -v) / Fes(Radiansθ 104 ), where d is the interplanar spacing, 0.5≤k≤1.0, 0.11≤λ≤0.16, uv≥0.005. The half-peak widths of the 003 and 104 planes of the single-crystalline sodium ion layered oxide material meet this condition, which can make the crystal plane structure grow in a preferential orientation, thereby inhibiting the change amplitude of the c-axis of the sodium ion layered oxide material during the charge and discharge process, so the structural phase change is suppressed, and the changes in the unit cell parameters a, b, and c axes before and after the phase change meet the relationship: Δc<(Δa+Δb) / γ, 1<γ<5, and the Δc value is low, indicating that the change amplitude of the c-axis is small.
[0034] The particle size of the sodium ion layered oxide material satisfies 4.0μm≤Dv50≤20.0μm. As an example, Dv50 can be but is not limited to 4.0μm, 5.0μm, 6.0μm, 7.0μm, 8.0μm, 9.0μm, 10.0μm, 11.0μm, 12.0μm, 13.0μm, 14.0μm, 15.0μm, 16.0μm, 17.0μm, 18.0μm, 19.0μm, and 20.0μm. The thickness of the single layer is 0.5-2.0 μm. As an example, the thickness can be, but is not limited to, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm. The specific surface area is 0.3-0.8 m 2 / g, as an example, the specific surface area can be but is not limited to 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g. The compacted density is 3.5~4.5g / m 3 As an example, the density may be, but is not limited to, 3.5 g / m 3 3.6g / m 3 3.7g / m 3 3.8g / m 3 , 3.9g / m 3 4.0g / m 3 4.1g / m 3 4.2g / m 3 4.3g / m 3 4.4g / m 3 4.5g / m 3 .
[0035] The method for preparing the single crystal sodium ion layered oxide material of the present invention comprises: (I) synthesizing Ni by coprecipitation reaction x Fe y Mn (1-x-y) (OH)2 precursor; (II) Ni x Fe y Mn (1-x-y) The (OH)2 precursor, sodium salt and flux are mixed and reacted at high temperature under oxidizing atmosphere.
[0036] In which, the preparation of the hydroxide precursor in step (I) can be carried out by using soluble nickel salt, soluble iron salt, and soluble manganese salt as raw materials, using alkali solution as a precipitant, and preparing a spherical nickel cobalt manganese hydroxide precursor through a coprecipitation method.
[0037] Specifically, a mixed solution of soluble nickel salt, iron salt and manganese salt is prepared according to the formula ratio, and an alkali solution is prepared. The mixed solution and the alkali solution are mixed in a reactor for grain growth. The alkali solution can be added in steps. When the particle size reaches the standard, a hydroxide precursor is obtained after aging. The soluble nickel salt, iron salt and manganese salt are one or more of sulfates, carbonates, nitrates and chlorates of nickel ions, cobalt ions and manganese ions, respectively. The concentration of the mixed solution is 1 to 3 mol / L. As an example, the concentration can be but not limited to 1 mol / L, 2 mol / L, and 3 mol / L. The alkali solution is selected from sodium hydroxide or ammonia water, and the alkali solution is used as a precipitant to obtain a hydroxide precursor. The concentration of the alkali solution is 5 to 10 mol / L. As an example, the concentration can be but not limited to 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, and 10 mol / L. The pH value in the reactor is 10-12, for example, it can be but not limited to 10, 11, 12, or the ammonia value in the reactor is 3-8g / L, for example, the ammonia value can be but not limited to 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L. The particle size Dv50 is 1.0-11.0μm, for example, it can be but not limited to 1.0μm, 2.0μm, 3.0μm, 4.0μm, 5.0μm, 6.0μm, 7.0μm, 8.0μm, 9.0μm, 10.0μm, 11.0μm. Nitrogen can be introduced into the reactor during the coprecipitation reaction, and the nitrogen flow rate is 3-8m 3 / h, as an example, the nitrogen flow rate can be but is not limited to 3m 3 / h、4m 3 / h、5m 3 / h、6m 3 / h、7m 3 / h、8m 3 / h. The temperature of the coprecipitation reaction can be 50-70°C. As an example, the temperature can be, but not limited to, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, and 70°C. The aging time can be 50-200min. As an example, the aging time can be, but not limited to, 50min, 80min, 100min, 120min, 140min, 160min, 180min, and 200min. Further, after aging, washing, drying, and sieving can also be included in sequence. Washing is distilled water washing at 50-100°C, and the washing time is 50-300min. As an example, the temperature of distilled water can be, but not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, and 100°C. The washing time may be, but is not limited to, 50 min, 80 min, 100 min, 120 min, 140 min, 160 min, 180 min, 200 min, 220 min, 240 min, 260 min, 280 min, 300 min. The drying temperature is 50-150°C. For example, the temperature may be, but is not limited to, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C. The drying time is 0.5-3.0 h. For example, the time may be, but is not limited to, 0.5 h, 1.0 h, 1.5 h, 2.0 h, 2.5 h, 3.0 h. A sieve of 100-400 mesh is used for sieving.
[0038] The sodium salt in step (II) includes one or more of sodium nitrate, sodium chloride and sodium carbonate. x Fe y Mn (1-x-y) The (OH)2 precursor accounts for 50-70% of its mass. As an example, it can be, but is not limited to, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%. The flux includes one or more of zirconium oxide, zirconium hydroxide, magnesium oxide, magnesium hydroxide, lanthanum oxide, lanthanum hydroxide, strontium carbonate, strontium hydroxide, titanium oxide and titanium hydroxide. Adding the flux can reduce the reaction temperature. The flux accounts for Ni x Fe y Mn (1-x-y)The mass of the (OH)2 precursor is 0.1-3.0%. As an example, it can be, but not limited to, 0.1%, 0.3%, 0.5%, 0.7%, 1.0%, 1.3%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%. The reaction temperature of the high temperature reaction is 850-1050°C. As an example, the temperature can be, but not limited to, 850°C, 880°C, 900°C, 930°C, 950°C, 980°C, 1000°C, 1030°C, 1050°C. The heating rate of the high temperature reaction is 1-5°C / min. As an example, the rate can be, but not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min. The reaction time of the high temperature reaction is 8 to 20 hours. As an example, the reaction time can be, but is not limited to, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, and 20 hours. The oxidizing atmosphere is air or oxygen. x Fe y Mn (1-x-y) The single crystal sodium ion layered oxide positive electrode material prepared by high temperature reaction of (OH)2 precursor, sodium salt and flux can be in the form of a round or square sheet.
[0039] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0040] Example 1
[0041] This embodiment is a single crystal sodium ion layered oxide material with a chemical formula of NaNi 0.33 Fe 0.33 Mn 0.33 O2.
[0042] The method for preparing the single crystal sodium ion layered oxide material of this embodiment includes the following steps.
[0043] (I) Preparation of Precursor
[0044] A mixed solution of nickel, cobalt and manganese salts with a total concentration of 1.5 mol / L was prepared by using nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of n(Ni):n(Fe):n(Mn)=0.33:0.33:0.33, and a sodium hydroxide solution with a concentration of 5 mol / L was prepared as a precipitant;
[0045] A certain volume of deionized water was introduced into the reactor, stirring and heating were started, and then the prepared sodium hydroxide solution was injected into the reactor through the liquid inlet pipe, and the pH value in the reactor was controlled to be 11.00 and the temperature was maintained at 65°C;
[0046] Continue to inject the metal salt mixed solution and the remaining sodium hydroxide solution into the reactor at the same time. During the reaction, the pH value in the reactor is 11.00±0.20, the stirring speed is 200r / min, the temperature is maintained at 65°C, and nitrogen is continuously introduced. In the early stage of the reaction, small particles generated in the reactor are discharged through the overflow port. The reaction is stopped when the central particle size of the particles produced in the reactor is about 8.5μm.
[0047] The reactants overflowed into the aging kettle, and after aging, they were centrifuged and washed. Then, the reactants were dried at 80°C, and after drying, they were sieved and iron removed to obtain Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 precursor.
[0048] (II) Put Ni 0.33 Fe 0.33 Mn 0.33 The (OH)2 precursor, sodium nitrate, zirconium oxide and magnesium oxide are mixed and reacted at high temperature in an air atmosphere. Sodium nitrate, zirconium oxide and magnesium oxide account for 1% and 2% of Ni, respectively. 0.33 Fe 0.33 Mn 0.33 The mass of (OH)2 precursor is 65%, 0.5%, and 1.0%. The heating rate of the high temperature reaction is 5℃ / min, the reaction temperature is 850℃, the reaction time is 20h, and the synthetic chemical formula is NaNi 0.33 Fe 0.33 Mn 0.33 Single crystal sodium ion layered oxide materials of O2.
[0049] The prepared single crystal sodium ion layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2 was tested by XRD. Single crystal sodium ion layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 The half-peak width of the 003 crystal plane of O2 is 0.126, and satisfies the equation: kλ / Radians(FWHM003) / Fes(Radiansθ 003 )≤d≤kλ / Radians(FWHM
[0050] 003 -u) / Fes(Radiansθ 003 ), the half-peak width of the 104 crystal plane is 0.103, which satisfies the equation: kλ / Radians(FWHM104) / Fes(Radiansθ 104 )≤d≤kλ / Radians(FWHM 104 -v) / Fes(Radiansθ104 ), where k = 0.9, λ = 0.1504, u = 0.065, v = 0.056. Single crystal sodium ion layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2 has a Dv50 of 5.2 μm, a single layer thickness of 0.6 μm, and a specific surface area of 0.7 m 2 / g, compacted density is 3.7g / m 3 . Single crystal sodium ion layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2 can effectively inhibit the structural phase change during the charge and discharge process, where the unit cell parameters c axis and a, b axis before and after the phase change satisfy the relationship: Δc<(Δa+Δb) / γ, where 1<γ<5. The unit cell parameters before and after charge and discharge are shown in Table 1.
[0051] Example 2
[0052] This embodiment is a single crystal sodium ion layered oxide material with a chemical formula of NaNi 0.35 Fe 0.30 Mn 0.35 O2.
[0053] The method for preparing the single crystal sodium ion layered oxide material of this embodiment includes the following steps.
[0054] (I) Preparation of Precursor
[0055] Nickel sulfate, cobalt sulfate and manganese sulfate are prepared into a mixed solution of nickel, cobalt and manganese salts with a total concentration of 2.5 mol / L according to a molar ratio of n(Ni):n(Fe):n(Mn)=0.35:0.30:0.35, and a sodium hydroxide solution with a concentration of 7 mol / L is prepared as a precipitant;
[0056] A certain volume of deionized water was introduced into the reactor, stirring and heating were started, and then the prepared sodium hydroxide solution was injected into the reactor through the liquid inlet pipe, and the pH value in the reactor was controlled to be 11.50 and the temperature was maintained at 70°C;
[0057] Continue to inject the metal salt mixed solution and the remaining sodium hydroxide solution into the reactor at the same time. During the reaction, the pH value in the reactor is 11.50±0.20, the stirring speed is 200r / min, the temperature is maintained at 70°C, and nitrogen is continuously introduced. In the early stage of the reaction, small particles generated in the reactor are discharged through the overflow port. The reaction is stopped when the central particle size of the particles produced in the reactor is about 10.0μm.
[0058] The reactant overflowed into the aging kettle, and after aging, it was centrifuged and washed. Then, the reactant was dried at 100°C, and after drying, it was sieved and iron removed to obtain Ni 0.35 Fe 0.30 Mn 0.35 (OH)2 precursor.
[0059] (II) Put Ni 0.35 Fe 0.30 Mn 0.35 The (OH)2 precursor, sodium nitrate, zirconium oxide and magnesium oxide are mixed and reacted at high temperature in an air atmosphere. Sodium nitrate, zirconium oxide and magnesium oxide account for 1% and 2% of Ni, respectively. 0.35 Fe 0.30 Mn 0.35 The mass of (OH)2 precursor is 70%, 1.0%, and 1.5%. The heating rate of the high temperature reaction is 5℃ / min, the reaction temperature is 880℃, the reaction time is 20h, and the synthetic chemical formula is NaNi 0.35 Fe 0.30 Mn 0.35 Single crystal sodium ion layered oxide materials of O2.
[0060] The prepared single crystal sodium ion layered oxide material NaNi 0.35 Fe 0.30 Mn 0.35 O2 was tested by XRD. Single crystal sodium ion layered oxide material NaNi 0.35 Fe 0.30 Mn 0.35 The half-peak width of the 003 crystal plane of O2 is 0.120 and satisfies the equation: kλ / Radians(FWHM003) / Fes(Radiansθ 003 )≤d≤kλ / Radians(FWHM 003 -u) / Fes(Radiansθ 003 ), the half-peak width of the 104 crystal plane is 0.115, which satisfies the equation: kλ / Radians(FWHM104) / Fes(Radiansθ 104 )≤d≤kλ / Radians(FWHM 104 -v) / Fes(Radiansθ 104 ), where k = 0.89, λ = 0.1504, u = 0.063, v = 0.059. Single crystal sodium ion layered oxide material NaNi 0.35 Fe 0.30 Mn 0.35 O2 has a Dv50 of 5.5 μm, a single layer thickness of 0.8 μm, and a specific surface area of 0.5 m 2 / g, compacted density is 3.6g / m 3. Single crystal sodium ion layered oxide material NaNi 0.35 Fe 0.30 Mn 0.35 O2 can effectively inhibit the structural phase change during the charge and discharge process, where the unit cell parameters c axis and a, b axis before and after the phase change satisfy the relationship: Δc<(Δa+Δb) / γ, where 1<γ<5. The unit cell parameters before and after charge and discharge are shown in Table 1.
[0061] Example 3
[0062] This embodiment is a single crystal sodium ion layered oxide material with a chemical formula of NaNi 0.30 Fe 0.35 Mn 0.35 O2.
[0063] The method for preparing the single crystal sodium ion layered oxide material of this embodiment includes the following steps.
[0064] (I) Preparation of Precursor
[0065] A mixed solution of nickel, cobalt and manganese salts with a total concentration of 1.5 mol / L was prepared by using nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of n(Ni):n(Fe):n(Mn)=0.30:0.35:0.35, and a sodium hydroxide solution with a concentration of 5 mol / L was prepared as a precipitant;
[0066] A certain volume of deionized water was introduced into the reactor, stirring and heating were started, and then the prepared sodium hydroxide solution was injected into the reactor through the liquid inlet pipe, and the pH value in the reactor was controlled to be 11.00 and the temperature was maintained at 65°C;
[0067] Continue to inject the metal salt mixed solution and the remaining sodium hydroxide solution into the reactor at the same time. During the reaction, the pH value in the reactor is 11.00±0.20, the stirring speed is 200r / min, the temperature is maintained at 65°C, and nitrogen is continuously introduced. In the early stage of the reaction, small particles generated in the reactor are discharged through the overflow port. The reaction is stopped when the central particle size of the particles produced in the reactor is about 8.5μm.
[0068] The reactants overflowed into the aging kettle, and after aging, they were centrifuged and washed. Then, the reactants were dried at 80°C, and after drying, they were sieved and iron removed to obtain Ni 0.30 Fe 0.35 Mn 0.35 (OH)2 precursor.
[0069] (II) Put Ni 0.30 Fe 0.35 Mn 0.35The (OH)2 precursor, sodium carbonate, lanthanum hydroxide and titanium oxide are mixed and reacted at high temperature in an air atmosphere. Sodium carbonate, lanthanum hydroxide and titanium oxide account for 1.3% and 1.5% of Ni, respectively. 0.30 Fe 0.35 Mn 0.35 The mass of (OH)2 precursor is 60%, 0.7% and 0.8%. The heating rate of the high temperature reaction is 3℃ / min, the reaction temperature is 900℃, the reaction time is 18h, and the synthetic chemical formula is NaNi 0.30 Fe 0.35 Mn 0.353 Single crystal sodium ion layered oxide materials of O2.
[0070] The prepared single crystal sodium ion layered oxide material NaNi 0.30 Fe 0.35 Mn 0.35 O2 was tested by XRD. Single crystal sodium ion layered oxide material NaNi 0.30 Fe 0.35 Mn 0.35 The half-peak width of the 003 crystal plane of O2 is 0.137 and satisfies the equation: kλ / Radians(FWHM003) / Fes(Radiansθ 003 )≤d≤kλ / Radians
[0071] (FWHM 003 -u) / Fes(Radiansθ 003 ), the half-peak width of the 104 crystal plane is 0.125, which satisfies the equation: kλ / Radians(FWHM104) / Fes(Radiansθ 104 )≤d≤kλ / Radians(FWHM 104 -v) / Fes(Radiansθ 104 ), where k = 0.9, λ = 0.1504, u = 0.061, v = 0.050. Single crystal sodium ion layered oxide material NaNi 0.30 Fe 0.35 Mn 0.35 The Dv50 of O2 is 4.5 μm, the thickness of the single layer is 1.0 μm, and the specific surface area is 0.8 m 2 / g, compacted density is 3.55g / m 3 . Single crystal sodium ion layered oxide material NaNi 0.30 Fe 0.35 Mn 0.35 O2 can effectively inhibit the structural phase change during the charge and discharge process, where the unit cell parameters c axis and a, b axis before and after the phase change satisfy the relationship: Δc<(Δa+Δb) / γ, where 1<γ<5. The unit cell parameters before and after charge and discharge are shown in Table 1.
[0072] Example 4
[0073] This embodiment is a single crystal sodium ion layered oxide material with a chemical formula of NaNi 0.25 Fe 0.25 Mn 0.50 O2.
[0074] The method for preparing the single crystal sodium ion layered oxide material of this embodiment includes the following steps.
[0075] (I) Preparation of Precursor
[0076] A mixed solution of nickel, cobalt and manganese salts with a total concentration of 1.5 mol / L was prepared by using nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of n(Ni):n(Fe):n(Mn)=0.25:0.25:0.50, and a sodium hydroxide solution with a concentration of 5 mol / L was prepared as a precipitant;
[0077] A certain volume of deionized water was introduced into the reactor, stirring and heating were started, and then the prepared sodium hydroxide solution was injected into the reactor through the liquid inlet pipe, and the pH value in the reactor was controlled to be 11.00 and the temperature was maintained at 65°C;
[0078] Continue to inject the metal salt mixed solution and the remaining sodium hydroxide solution into the reactor at the same time. During the reaction, the pH value in the reactor is 11.00±0.20, the stirring speed is 200r / min, the temperature is maintained at 65°C, and nitrogen is continuously introduced. In the early stage of the reaction, small particles generated in the reactor are discharged through the overflow port. The reaction is stopped when the central particle size of the particles produced in the reactor is about 8.5μm.
[0079] The reactants overflowed into the aging kettle, and after aging, they were centrifuged and washed. Then, the reactants were dried at 80°C, and after drying, they were sieved and iron removed to obtain Ni 0.25 Fe 0.25 Mn 0.50 (OH)2 precursor.
[0080] (II) Put Ni 0.25 Fe 0.25 Mn 0.50 The (OH)2 precursor, sodium hydroxide, titanium oxide and magnesium oxide are mixed and reacted at high temperature in an air atmosphere. Sodium hydroxide, titanium oxide and magnesium oxide account for 1% and 2% of Ni 0.25 Fe 0.25 Mn 0.50 The mass of (OH)2 precursor is 60%, 1.0%, and 0.8%. The heating rate of the high temperature reaction is 2.5℃ / min, the reaction temperature is 920℃, the reaction time is 18h, and the synthetic chemical formula is NaNi 0.25 Fe 0.25 Mn0.50 Single crystal sodium ion layered oxide materials of O2.
[0081] The prepared single crystal sodium ion layered oxide material NaNi 0.25 Fe 0.25 Mn 0.50 O2 was tested by XRD. Single crystal sodium ion layered oxide material NaNi 0.25 Fe 0.25 Mn 0.50 The half-peak width of the 003 crystal plane of O2 is 0.116, and satisfies the equation: kλ / Radians(FWHM003) / Fes(Radiansθ 003 )≤d≤kλ / Radians
[0082] (FWHM 003 -u) / Fes(Radiansθ 003 ), the half-peak width of the 104 crystal plane is 0.112, which satisfies the equation: kλ / Radians(FWHM104) / Fes(Radiansθ 104 )≤d≤kλ / Radians(FWHM 104 -v) / Fes(Radiansθ 104 ), where k = 0.9, λ = 0.1504, u = 0.063, v = 0.062. Single crystal sodium ion layered oxide material NaNi 0.25 Fe 0.25 Mn 0.50 O2 has a Dv50 of 5.4 μm, a single layer thickness of 0.9 μm, and a specific surface area of 0.8 m 2 / g, compacted density is 3.73g / m 3 . Single crystal sodium ion layered oxide material NaNi 0.25 Fe 0.25 Mn 0.50 O2 can effectively inhibit the structural phase change during the charge and discharge process, where the unit cell parameters c axis and a, b axis before and after the phase change satisfy the relationship: Δc<(Δa+Δb) / γ, where 1<γ<5. The unit cell parameters before and after charge and discharge are shown in Table 1.
[0083] Comparative Example 1
[0084] This comparative example is a single crystal sodium ion layered oxide material with a chemical formula of NaNi 0.20 Fe 0.60 Mn 0.20 O2.
[0085] The method for preparing the single crystal sodium ion layered oxide material of this embodiment includes the following steps.
[0086] (I) Preparation of Precursor
[0087] A mixed solution of nickel, cobalt and manganese salts with a total concentration of 1.5 mol / L was prepared by using nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of n(Ni):n(Fe):n(Mn)=0.20:0.60:0.20, and a sodium hydroxide solution with a concentration of 5 mol / L was prepared as a precipitant;
[0088] A certain volume of deionized water was introduced into the reactor, stirring and heating were started, and then the prepared sodium hydroxide solution was injected into the reactor through the liquid inlet pipe, and the pH value in the reactor was controlled to be 11.00 and the temperature was maintained at 65°C;
[0089] Continue to inject the metal salt mixed solution and the remaining sodium hydroxide solution into the reactor at the same time. During the reaction, the pH value in the reactor is 11.00±0.20, the stirring speed is 200r / min, the temperature is maintained at 65°C, and nitrogen is continuously introduced. In the early stage of the reaction, small particles generated in the reactor are discharged through the overflow port. The reaction is stopped when the central particle size of the particles produced in the reactor is about 8.5μm.
[0090] The reactants overflowed into the aging kettle, and after aging, they were centrifuged and washed. Then, the reactants were dried at 80°C, and after drying, they were sieved and iron removed to obtain Ni 0.20 Fe 0.60 Mn 0.20 (OH)2 precursor.
[0091] (II) Put Ni 0.20 Fe 0.60 Mn 0.20 The (OH)2 precursor, sodium nitrate, zirconium oxide and magnesium oxide are mixed and reacted at high temperature in an air atmosphere. Sodium nitrate, zirconium oxide and magnesium oxide account for 1% and 2% of Ni, respectively. 0.20 Fe 0.60 Mn 0.20 The mass of (OH)2 precursor is 65%, 0.5%, and 1.0%. The heating rate of the high temperature reaction is 5℃ / min, the reaction temperature is 850℃, the reaction time is 20h, and the synthetic chemical formula is NaNi 0.20 Fe 0.60 Mn 0.20 Single crystal sodium ion layered oxide materials of O2.
[0092] The prepared single crystal sodium ion layered oxide material NaNi 0.20 Fe 0.60 Mn 0.20 O2 was tested by XRD. Single crystal sodium ion layered oxide material NaNi 0.20 Fe 0.60 Mn 0.20The half-peak width of the 003 crystal plane of O2 is 0.155, and does not satisfy the equation: kλ / Radians(FWHM003) / Fes(Radiansθ 003 )≤d≤kλ / Radians(FWHM 003 -u) / Fes(Radiansθ 003 ), the half-peak width of the 104 crystal plane is 0.147, which does not satisfy the equation: kλ / Radians(FWHM 104) / Fes(Radiansθ 104 )≤d≤kλ / Radians(FWHM 104 -v) / Fes(Radiansθ 104 ), where k = 0.9, λ = 0.1504, u = 0.065, v = 0.056. Single crystal sodium ion layered oxide material NaNi 0.33 Fe 0.33 Mn 0.33 O2 has a Dv50 of 5.0 μm, a single layer thickness of 0.6 μm, and a specific surface area of 1.3 m 2 / g, compacted density is 3.2g / m 3 . Single crystal sodium ion layered oxide material NaNi 0.20 Fe 0.60 Mn 0.20 O2 can effectively inhibit the structural phase change during the charge and discharge process, where the unit cell parameters c axis and a, b axis before and after the phase change satisfy the relationship: Δc<(Δa+Δb) / γ, where 1<γ<5. The unit cell parameters before and after charge and discharge are shown in Table 1.
[0093] The single crystal sodium ion layered oxides of Examples 1 to 4 and Comparative Example 1 were subjected to a cycle performance test.
[0094] Cyclic performance test: The single crystal sodium ion layered oxides of Examples 1 to 4 and Comparative Example 1 were used as active materials, respectively, mixed with binder PVDF and conductive agent (Super-P) in a mass ratio of 95:1.5:3.5, and an appropriate amount of N-vinyl pyrrolidone was added as a solvent to prepare a slurry, which was coated on aluminum foil, and vacuum dried and rolled to prepare a negative electrode sheet. Metallic sodium was used as the counter electrode, 1 mol / L NaPF6 and a three-component mixed solvent of EC:DMC:EMC=1:1:1 (v / v) were used to form an electrolyte, and a polypropylene microporous membrane was used as a diaphragm, and a CR2032 button cell was assembled in a glove box filled with inert gas. The charge and discharge test of button battery was carried out on the battery test system of Wuhan Landian Electronics Co., Ltd. at 25℃. The charging process was 0.1C constant current charging to 4.0V and then constant voltage charging to a cut-off current of 0.05C. The discharge process was 0.1C constant current discharge to 2.0V. After 50 cycles, the discharge capacity at the 50th cycle was obtained, and the capacity retention rate at the 50th cycle was calculated.
[0095] Table 1 Cyclic performance and physical properties of each embodiment and comparative example
[0096]
[0097] From the results in Table 1, it can be seen that the unit cell parameters of the single crystal sodium ion layered oxide materials of Examples 1 to 4 conform to the relationship Δc<(Δa+Δb) / γ, where 1<γ<5, and the capacity retention rate at the 50th cycle is significantly higher than that of Comparative Example 1. This is because the 003 crystal plane half-width and the 104 crystal plane half-width of the crystal structure of the single crystal sodium ion layered oxide materials of Examples 1 to 4 meet certain conditions, which can make the crystal plane structure grow in a preferential orientation, thereby suppressing the c-axis change amplitude of the sodium ion layered oxide material during the charge and discharge process, thereby suppressing the structural phase change.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A single crystal sodium ion layered oxide material, characterized in that: The chemical formula is NaNi x Fe y Mn (1-x-y) O2, 0.15≤x≤0.60, 0.20≤y≤0.40, the half-peak width of the 003 crystal plane and the half-peak width of the 104 crystal plane of the crystal structure meet the following conditions: kλ / Radians(FWHM003) / Fes(Radiansθ 003 )≤d≤kλ / Radians(FWHM 003 -u) / Fes(Radiansθ 003 ),kλ / Radians(FWHM104) / Fes(Radiansθ 104 )≤d≤kλ / Radians(FWHM 104 -v) / Fes(Radiansθ 104 ), where d is the interplanar spacing, 0.5≤k≤1.0, 0.11≤λ≤0.16, uv≥0.
005.
2. The single crystal sodium ion layered oxide material according to claim 1, characterized in that: The particle size satisfies 4.0μm≤Dv50≤20.0μm.
3. The single crystal sodium ion layered oxide material according to claim 1, characterized in that: The thickness of the single layer is 0.5 to 2.0 μm.
4. The single crystal sodium ion layered oxide material according to claim 1, characterized in that: The structural phase transition during the charge and discharge process can be suppressed, and the changes in the unit cell parameters a, b, and c axes before and after the phase transition satisfy the relationship: Δc<(Δa+Δb) / γ, 1<γ<5.
5. The single crystal sodium ion layered oxide material according to claim 1, characterized in that: Specific surface area is 0.3~0.8m 2 / g.
6. The single crystal sodium ion layered oxide material according to claim 1, characterized in that: The compacted density is 3.5~4.5g / m 3 .
7. The method for preparing a single-crystalline sodium ion layered oxide material according to any one of claims 1 to 6, characterized in that: Includes steps: (I) Synthesis of Ni by coprecipitation reaction x Fe y Mn (1-x-y) (OH)2 precursor; (II) The Ni x Fe y Mn (1-x-y) The (OH)2 precursor, sodium salt and flux are mixed and reacted at high temperature under oxidizing atmosphere.
8. The method for preparing a single-crystalline sodium ion layered oxide material according to claim 7, characterized in that: The invention comprises at least one of the following features (1) to (8): (1) The sodium salt includes one or more of sodium nitrate, sodium chloride and sodium carbonate; (2) The sodium salt accounts for the Ni x Fe y Mn (1-x-y) 50-70% of the mass of (OH)2 precursor; (3) The flux includes one or more of zirconium oxide, zirconium hydroxide, magnesium oxide, magnesium hydroxide, lanthanum oxide, lanthanum hydroxide, strontium carbonate, strontium hydroxide, titanium oxide and titanium hydroxide; (4) The flux accounts for the Ni x Fe y Mn (1-x-y) 0.1-3.0% of the mass of (OH)2 precursor; (5) The oxidizing atmosphere is air or oxygen; (6) The reaction temperature of the high temperature reaction is 850-1050° C.; (7) The heating rate of the high temperature reaction is 1 to 5°C / min; (8) The reaction time of the high temperature reaction is 8 to 20 hours.
9. Use of the single-crystalline sodium ion layered oxide material prepared by the single-crystalline sodium ion layered oxide material according to any one of claims 1 to 6 or the method for preparing the single-crystalline sodium ion layered oxide material according to any one of claims 7 to 8 in a sodium ion battery.
10. A secondary battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The positive electrode material comprises the single crystal sodium ion layered oxide material according to any one of claims 1 to 6 or the single crystal sodium ion layered oxide material prepared by the preparation method of the single crystal sodium ion layered oxide material according to any one of claims 7 to 8.